Dynamics of ideas about the concept of epileptic psychosis - Y. A. Yakovleva; M. Y. Kissin; Y. V. Popov; A. A. Pichikov; N. Y. Safonova; T. M. Goguadze (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Introduction: psychosis in epilepsy is more common than in the general population. The frequency of psychotic mental disorders varies from 0,5% to 10%. The article presents the dynamics of the development of the concept of epileptic psychosis, depending on the evolutionary approaches to the study of the problem of mental disorders in epilepsy. Materials and methods: the analysis of Russian—and English language articles in scientific databases on keywords from 1971 to 2011 was carried out. Results: the first systematic descriptions of mental disorders occurring in epilepsy date back to the 19th century. The contribution of foreign and domestic authors to the study of the problem is described. There are six main periods of the concept formation, including the definitions of the concept of epileptic psychosis, the dynamics of clinical manifestations, the role of the influence of biological, personal and social factors in the genesis and development of psychotic disorders in epilepsy. The following risk factors for the development of psychosis are considered: the form of epilepsy; age of onset of seizures, lateralization of the epileptic focus, gender, and drug therapy. Variants of classification approaches to the problem are presented. The article discusses the differences in the systematization of «endoform» syndromes, as well as the parallels between schizophrenia and psychoses in epilepsy. The dynamics of scientific views on the interest in the formation of epileptic psychoses in various parts of the brain: the temporal lobe (amygdala, hippocampus, paralimbic zones and parahippocampal bend), as well as GABA-ergic neurons of the upper tubercles of the quadriplegic, posterior hypothalamus and serotonergic neurons of the dorsal suture and noradrenergic neurons of the blue spot are reflected. The association of psychopathological manifestations with neurophysiological, biochemical, genetic and morphofunctional correlates is noted. The authors‘ interest in psychoses associated with the use of antiepileptic drugs is emphasized. Conclusion: despite all attempts to systematize these conditions, the factors that provoke the development of psychoses in patients with epilepsy, their structure and prognosis remain poorly predictable and require further in-depth study.